Perancangan Sistem Informasi Pondok Pesantren Berbasis Aplikasi Dekstop Dengan Metode Extreme Programming - Andhika Noviantara; Luzen Aji Budiman; Raden Azka Hermanto; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
In the current era of globalization, information systems using highly sophisticated and modern computer technology will make it easier for us to perform data processing that can save time, space and costs. And the useful results of the information obtained will be very satisfying and useful for an institution or agency that uses it. Processing data and information quickly, precisely and efficiently is an important thing that is needed for institutions or agencies, one of which is the Bahrul Hadi Arrahmani Islamic Boarding School Foundation. The process of collecting data on santri/santriwati so far is still using the manual method; when collecting data; the administrators are still manual, with the existence of this desktop application technology, it is hoped that it can assist administrators in carrying out data collection efficiently. A good information system can help improve efficiency and productivity in the daily operations of a boarding school. The Extreme Programming (XP) method is a software development methodology that involves practices such as adaptive planning,continuous testing, and iterative delivery. This research was conducted by applying the XP principles in each stage of the development of Islamic boarding school information systems. The development stages include planning, needs analysis, design, implementation, testing, and delivery. During the development phase, the XP method is implemented by performing adaptive planning, continuous testing, and iterative delivery to ensure the quality of the information system. The results of this study are Islamic boarding school information systems that can increase efficiency and productivity in the daily operations of Islamic boarding schools.